Pelatihan Pemanfaatan Artificial Intelligence untuk Pendidikan Al-Quran di Yayasan Nurul Qurani Bekasi - Andy Achmad Hendharsetiawan; Rafika Sari; Aida Fitriyani; Khairunnisa Fadhilla Ramdhania; Rakhmi Khalida; Lisa Adhani (Journal Of Computer Science Contributions (JUCOSCO), 2026)
Artificial intelligence literacy is increasingly relevant to Quranic education, especially for supporting recitation practice, memorization, and access to learning resources. This community service program aimed to strengthen the conceptual understanding and responsible use of artificial intelligence among students and educators at the Nurul Qurani Islamic Da'wah and Education Foundation in Bekasi City. The activity was conducted on 29 December 2025 through preliminary coordination, material preparation, an interactive presentation, demonstrations of Qaraa and ngaji.ai, guided discussion, and descriptive evaluation. Data were obtained from facilitator observations, oral questions and answers, participant responses during demonstrations, field notes, and activity documentation. The program introduced basic artificial intelligence, machine learning, generative artificial intelligence, speech recognition, potential applications in Quranic learning, and ethical issues. Qualitative findings indicate that participants were able to recognize the distinction between artificial intelligence as a supporting tool and the irreplaceable pedagogical and spiritual role of teachers. Participants also identified opportunities for immediate feedback, independent repetition, learning progress monitoring, and semantic information retrieval, while acknowledging limitations related to accuracy, privacy, bias, and unverified religious information. The originality of this program lies in contextualizing artificial intelligence literacy within Quranic education and combining technical demonstrations with ethical and religious verification principles. Future programs should add validated pre-test and post-test instruments, longer hands-on practice, and structured mentoring for educators.